2018
DOI: 10.3899/jrheum.170710
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Metaanalysis of Antirheumatic Drugs and Vaccine Immunogenicity in Rheumatoid Arthritis

Abstract: Antirheumatic drugs may limit humoral responses to vaccination as evidenced by pneumococcal responses with MTX exposure; however, they are safe and should not preclude immunization against vaccine-preventable disease. Vaccination should be considered in all patients with RA and encouraged as part of routine care. (Systematic review registration number: PROSPERO 2016: CRD42016048093.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
1
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(74 citation statements)
references
References 46 publications
4
62
1
7
Order By: Relevance
“…80 In terms of impairing vaccine immunogenicity, prednisone greater than 10 to 20 mg per day and rituximab have the greatest effect on influenza and pneumococcal vaccines in persons with RA. 74,[81][82][83][84] Tumor necrosis factor-a (TNF-a) inhibitors do not appear to affect the immune response to influenza and pneumococcal vaccines in persons with RA. 81 Some studies in persons with inflammatory bowel disease on TNF-a inhibitors have shown decreased antibody titers to hepatitis A, hepatitis B, and influenza vaccines compared with healthy controls.…”
Section: Autoimmune Inflammatory Rheumatic Diseases and Immunosuppresmentioning
confidence: 99%
See 1 more Smart Citation
“…80 In terms of impairing vaccine immunogenicity, prednisone greater than 10 to 20 mg per day and rituximab have the greatest effect on influenza and pneumococcal vaccines in persons with RA. 74,[81][82][83][84] Tumor necrosis factor-a (TNF-a) inhibitors do not appear to affect the immune response to influenza and pneumococcal vaccines in persons with RA. 81 Some studies in persons with inflammatory bowel disease on TNF-a inhibitors have shown decreased antibody titers to hepatitis A, hepatitis B, and influenza vaccines compared with healthy controls.…”
Section: Autoimmune Inflammatory Rheumatic Diseases and Immunosuppresmentioning
confidence: 99%
“…74,[81][82][83][84] Tumor necrosis factor-a (TNF-a) inhibitors do not appear to affect the immune response to influenza and pneumococcal vaccines in persons with RA. 81 Some studies in persons with inflammatory bowel disease on TNF-a inhibitors have shown decreased antibody titers to hepatitis A, hepatitis B, and influenza vaccines compared with healthy controls. [85][86][87][88][89] However, most persons achieved seroprotective antibody titers.…”
Section: Autoimmune Inflammatory Rheumatic Diseases and Immunosuppresmentioning
confidence: 99%
“…Among the SRs/SRMAs that covered a similar topic, the observed corrected covered areas varied greatly. Indeed, the corrected covered area of three SRMAs on systemic lupus erythematosus [54][55][56] and another three SRMAs on rheumatoid arthritis [47,57,63] showed very high corrected covered areas (73.7% and 21.1%, respectively), while three SRs on cancer patients [46,51,60] and two SRMAs on transplant patients [45,52] showed substantially lower corrected covered areas, which were deemed "moderate" (6.6% and 8.9%, respectively). Table 4 summarizes the evidence synthesis on the effect of any immunosuppressive condition on IV-induced immunogenicity.…”
Section: Immunosuppressive Conditionsmentioning
confidence: 99%
“…К этим вакцинам относятся гриппозные, пневмококковые, противостолбнячные, а также вакцины против гепатитов А/В и ВПЧ. В большинстве работ применение этих вакцин позволяло достичь адекватных уровней иммуногенности при отсутствии новых данных в отношении безопасности, хотя катамнестический период в этих исследованиях был коротким [8][9][10].…”
Section: рекомендации по вакцинации взрослых больных иврзunclassified